Linkage between knowledge management practices towards library user’s satisfaction at Malaysian University Libraries - Che Rusuli, Muhamad Saufi (2014)
Academic library services have begun to apply various knowledge management (KM) practices in the provision of library services. KM has been developed to enhance the use of organizational knowledge through practices and organizational learning. KM practices include the creation, capture and/or acquisition of knowledge, its retention and organization, its dissemination and re-use, and general responsiveness to the new knowledge. The focus of this research is the assessment of KM practices, particularly creation, acquisition, capture, sharing, recording and preservation, and their effects on Library User’s Satisfaction (LUS) in Malaysian university libraries. The objective of this research is the development of a model to enhance KM processes (i.e. Creation, acquisition, capturing, sharing, recording, and preserving) and to improve library users’ satisfaction. A quantitative approach in research methodology is employed (e.g. Questionnaire) for the purpose of generating new knowledge and understanding of library concerns. The findings of this research show that the overall KM practice at six Malaysian university libraries is at a high level. The findings from the structural model indicated that two KM processes, namely knowledge creation and acquisition, are not supported in terms of KM practices at Malaysian university libraries. Other KM processes, namely capturing, sharing, recording, and preserving are fully supported towards KM practices in the library. Hence, the major contribution of this research is a model, namely KM Practice-Library User’s Satisfaction (KMP-LUS) highlighting six KM processes based on strong Structural Equation Modeling (SEM) fit indices.